Інформативність гормональних маркерів ризику метаболічних порушень в осіб із різною масою тіла - Misiura, K.V. (Ендокринологія | Endokrynologia, 2018)
The objective of the work is to perform comprehensive evaluation of correlations between fractalkine, clusterin, vaspin and omentin levels in the residents of Kharkiv, as representatives of Ukrainian population, related to their body mass index, adipose tissue contents, fat accumulation degree and topography, blood insulin level, HOMA insulin resistance index. Materials and Methods. 250 residents of Kharkiv were examined (mean age 65.48±11.86 year). Body mass index was calculated, waist and hip circumferences were measured in the observed patients; bioimpedance technique was used to determine adipose, relative adipose and active body cell masses; fractalkine, clusterin, vaspin, omentin and insulin circulatory levels were determined with immunoassay technique; HOMA insulin resistance index was calculated. Results. Obese patients demonstrated reliably (р<0.001) higher levels of blood fractalkine, clusterin, vaspin, and lower contents of omentin compared to those with normal and excess body mass. Statistically significant (p<0.001) correlations of the examined peptides, anthropometric features, parameters of body composition, insulin and HOMA index were obtained. It was revealed that insulin resistant Ukrainian population representatives showed average fractalkine blood contents at the level of (937.20±87.08) ng/mL; clusterin — (126.16±16.59) ng/mL; vaspin — (671.39±135.54) ng/mL, and omentin (385.47±70.08) ng/mL. Clusterin, fractalkine, vaspin and omentin blood levels regression equations related to anthropometric parameters and НОМА index were calculated. Conclusions. Correlation between the increasing body mass (first of all due to adipose mass) and insulin and peptides blood contents which are markers of adipose tissue local inflammation, systemic low-intense in flammation in the body and development of cardial pathology was proved for the representatives of Ukrainian population.